A comparative morphological study of the sixth and seventh spinous processes of the cervical vertebrae in extinct and extant species of Equus. - May-Davis, Sharon; Hunter, Robert; Brown, Wendy (Vertebrate Anatomy Morphology Palaeontology, 2021)
The lateral profile of the 6th and 7th cervical spinous processes (CSPs) were examined in four extant species of Equus (n=33); E. caballus (n=26), E. przewalskii (n=3), E. quagga boehmi (n=1), E. asinus (n=3) and compared to pre-domesticated Equus specimens (n=66) representing three known species: E. occidentalis (n=56), E. mosbachensis (n=2), E. curvedins/insulatis (n=1) and unknown Equus species (n=7) from five museums. Six common morphological profiles were revealed: cuneate, curvate, falcate, rudimentary, scalenate, and truncate. For the 6th CSP, the distribution of these morphologies amongst extant Equus is: cuneate, only E. asinus; curvate, E. caballus and E. przewalskii always in combination with ligamentum lamina nuchae (lig. lamina nuchae) attachments from the 2nd through to 7th CSP inclusive; falcate, E. caballus and E. przewalskii always in combination with lig. lamina nuchae attachments from the 2nd through to 7th CSP inclusive; rudimentary, E. caballus always associated with lig. lamina nuchae attachments from the 2nd through to 5th CSP inclusive; scalenate, E. caballus in association with lig. lamina nuchae attachments from the 2nd through to 5th (n=11) or 7th (n=4) CSP inclusive; truncate, not present. The 6th CSP in museum specimens of Equus exhibits one of four profiles: cuneate (n=10), curvate (n=14), scalenate (n=11) and truncate (n=4). For the 7th CSP, the distribution of these morphologies amongst extant Equus is: curvate, E. caballus mostly associated with lig. lamina nuchae attachments from the 2nd through to 5th CSP inclusive, falcate, E. caballus mostly associated with lig. lamina nuchae attachments from the 2nd through to 7th CSP inclusive, scalenate, E. caballus associated with lig. lamina nuchae attachments from the 2nd through to 5th CSP inclusive. Only Rancho La Brea and Tar Pits Museum provided samples suitable for examination of the 7th CSP. These exhibited four profiles: curvate (n=7), falcate (n=11), scalenate (n=2), and truncate (n=7). These findings suggest that the lateral profile of the 6th CSP is of potential use in identification of species; attachments of the lig. lamina nuchae alter the morphology of the 6th and 7th CSP; and that attachments of the lig. lamina nuchae on the 2nd to 7th CSP were likely present in species of Equus prior to domestication.